Integrative taxonomy of central European parasitic flatworms of the family Prosthogonimidae Lühe, 1909 (Trematoda: Plagiorchiida) - Heneberg, Petr; Sitko, Jiljí; Bizos, Jiří (Parasitology international, 2015)
Species of the family Prosthogonimidae are considered the most pathogenic poultry trematodes worldwide, affecting particularly low intensity farming in rural areas. Adults of Prosthogonimus occur mainly in the bursa of Fabricius, oviduct and cloaca of ducks, geese, fowl and other birds feeding at least occasionally on dragonflies or damselflies (Odonata). We analyzed the central European species of the Prosthogonimidae, namely Prosthogonimus cuneatus, Prosthogonimus ovatus, Prosthogonimus pellucidus and Prosthogonimus rarus. We sequenced three nuclear (ITS2) and mitochondrial (CO1, ND1) DNA loci of four species isolated from Anas clypeata, Anas strepera, Anas platyrhynchos, Aythya ferina, Passer domesticus and Turdus merula. Intra- and inter-specific sequence variability revealed that all four species represent distinct well-defined entities. Our data, combined with previously published studies, suggest the return of the name Prosthogonimus rarus Braun, 1901 for Schistogonimus rarus (Braun, 1901). The genus name Schistogonimus Lühe, 1909 is considered a junior synonym of Prosthogonimus Lühe, 1899. We identified the existence of two clades, one represented by P. cuneatus and P. pellucidus, and another one formed by P. ovatus and P. rarus. We also provide comparative measurements of these four central European prosthogonimids, and address their tissue specificity, host-specific prevalence (based on the extensive bird cohort examined in years 1962-2014), and for some bird hosts we address also differences in the prevalence of Prosthogonimus spp. in natural and near-natural wetlands in comparison with fishponds utilized for intense carp production. We provide an updated key to European Prosthogonimus spp. based on their morphological characters.
Keywords: druhová specificita; Animals; Czech Republic; protozoální DNA; mezerníky ribozomální DNA; Poland; zvířata; molekulární sekvence - údaje; mitochondriální DNA; Passeriformes; Base Sequence; DNA, Mitochondrial; DNA, Protozoan; Phylogeny; sekvence nukleotidů; fylogeneze; Anseriformes; Trematode Infections; Polsko; Trematoda; Molecular Sequence Data; infekce červy třídy Trematoda; Česká republika; Bird Diseases; DNA, Ribosomal Spacer; nemoci ptáků; Species Specificity